2020
DOI: 10.1002/jez.b.22988
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the acoustic startle response of Mexican cavefish

Abstract: The ability to detect threatening stimuli and initiate an escape response is essential for survival and under stringent evolutionary pressure. In diverse fish species, acoustic stimuli activate Mauthner neurons, which initiate a C-start escape response. This reflexive behavior is highly conserved across aquatic species and provides a model for investigating the neural mechanism underlying the evolution of escape behavior. Here, we characterize evolved differences in the C-start response between populations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
4
10
0
Order By: Relevance
“…S1A) than surface fish. These findings are consistent with Paz et al (2020), who found cavefish have reduced angular velocity during a C-start (escape) response, differences observed as early as 6 days post fertilization. Providing support that these differences are not a consequence of laboratory conditions, video recordings of wild cavefish (Pachón cave) and wild surface fish (Rio Choy) swimming revealed surface fish incorporate sustained moderate swimming – a form of rheotaxis required to remain stationary against the river current – interspersed by vigorous burst-like swimming (Movie S2A).…”
Section: Resultssupporting
confidence: 92%
“…S1A) than surface fish. These findings are consistent with Paz et al (2020), who found cavefish have reduced angular velocity during a C-start (escape) response, differences observed as early as 6 days post fertilization. Providing support that these differences are not a consequence of laboratory conditions, video recordings of wild cavefish (Pachón cave) and wild surface fish (Rio Choy) swimming revealed surface fish incorporate sustained moderate swimming – a form of rheotaxis required to remain stationary against the river current – interspersed by vigorous burst-like swimming (Movie S2A).…”
Section: Resultssupporting
confidence: 92%
“…To assess escape response kinematics, plates containing fish in individual wells were fastened to a small vibration excitor and the response to escape-inducing vibration was measured with a high-speed camera (Figure 2D). The angular speed of cavefish was reduced, approaching significance (P=0.06), while the peak angle was also reduced (Figure 2E,F), consistent with a previous report that the escape response is blunted in cavefish (Paz et al 2020). Finally, we measured locomotor activity in cavefish because it is a critical for aspects of predator avoidance and foraging.…”
Section: Resultssupporting
confidence: 89%
“…Cave-dwelling forms have converged on distinct morphological traits, including albinism and eye loss (Jeffery 2020). In addition, cavefish evolved numerous behavioral changes including different prey capture, startle response, and increased locomotor activity (Duboué et al 2011;Lloyd et al 2018;Paz et al 2020). Overall these changes are thought to be critical for foraging in the absence of visual cues (Yoshizawa 2015;Keene and Duboue 2018;McGaugh et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Like morphology, neural circuits can adapt to the environment. Of these, many circuits are sensory and regulate essential behaviors such as foraging, navigation, and escapes ( Blin et al, 2018 ; Hoke et al, 2012 ; Hüppop, 1987 ; Paz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%